'Girls can like boy toys': junior primary school children's understandings of feminist picture books. Issue 7 (9th November 2016) - Bartholomaeus, Clare
Abstract : Few studies have examined children's understandings of feminist picture books, and thus their potential usefulness for disrupting dominant discourses and providing alternate storylines. This article draws on research conducted in Australia with a class of 6- and 7-year-olds, examining students' responses to four feminist picture books. The students provided diverse responses to the books, at times reflecting what I viewed as the (feminist) messages of the books and sometimes picking up on other themes or (re)interpreting them as supporting dominant gender discourses. The challenges to understanding the books in straightforward ways related both to the books themselves as well as the gender discourses available to the students. This article argues that there are three key challenges to the feminist potential of these books: a reliance on categories of 'girl' and 'boy', children's lack of identification with book characters, and the influence of intertextual knowledge.